State-Owned Enterprises in the Russian Federation : Employment Practices, Labor Markets, and Firm Performance - World Bank Group (World Bank, Washington, DC, 2019)
Low productivity and the competitiveness of Russian firms have been among Russia's primary economic challenges over the past decade. The Government of Russia (GoR) has made boosting productivity a policy priority and since 2012 has rolled out several visible policy initiatives to strengthen employment practices in firms to raise their productivity and positive spillovers, including the 2012 Plan for Raising the Productivity of Companies, the 2018-2024 National Project on Labor Productivity, and 2018-2019 National Plan for Competition Development. The objective of this report is to contribute to this productivity agenda by analyzing the employment practices of state-owned enterprises (SOEs), their implications for labor supply and internal firm capabilities, and the influence of state policy. SOEs contribute a significant share of output and employment in Russia's economy and academic recent research shows that they have lower productivity than private sector firms. The implications of SOE employment practices—compensation and management—on overall productivity however, has not been investigated, a gap that this report aims to fill by analyzing the following questions: What are SOE employment practices and how do they compare to international and private sector benchmarks? How do SOE employment practices, particularly compensation, affect allocation of labor across firms? How do SOE compensation and management practices shape their internal capabilities? How does government financial and non-financial support to SOEs influence these employment practices? Taking the level and form of government participation in the economy as a given, the report focuses primarily on the sector's current practices, and how government policies towards the sector can be improved to boost SOE performance and positive spillovers. We explore these questions using five Russian microlevel datasets, including worker and firm surveys and a large firm register. The report utilizes a taxonomy of SOEs that includes state SOEs which have 100 percent government ownership, and mixed SOEs which have some share of state ownership that is less than 100 percent. The report finds that Russian SOEs pay an overall compensation premium and that this premium contributes to labor shortages in the private sector. While overall the SOE sector has a small wage penalty, wage differentials with the private sector vary by type and size of the SOEs. Mixed SOEs pay a small wage premium over the private sector while state SOEs have a small wage penalty. Both types of SOEs pay a wage premium in competitive settings. SOEs have an overall compensation premium as they provide more generous benefits like paid vacations, maternity leave, and training than private sector firms.